Intussusception in a premature neonate: A rare and often misdiagnosed clinical entity - Advait Prakash; Bhavesh Doshi; Sangram Singh; Tanmay Vyas; Anvesh Jain (Wolters Kluwer Medknow Publications, 2015)
Intussusception is a very rare cause of intestinal obstruction in neonates. It is of extremely rare occurrence among premature neonates. We present a case of 11-day-old premature neonate who presented with abdominal distension, intolerance to feeds, vomiting, significant bilious aspirate and bleeding per rectum. The initial diagnosis of necrotizing enterocolitis (NEC) led to a delay in the diagnosis. On exploratory laparotomy, it turned out to be a case of ileo-colic intussusception with Meckel's diverticulum as a lead point. This site of intussusception (ileo-colic) and presence of a lead point among premature neonate is of exceedingly rare occurrence and very few such cases have been reported. In this article, the published work about clinical features and management on intussusceptions in premature neonates has been reviewed. The authors intend to highlight the difficulty in distinguishing the NEC and intussusception. Subtle clinical and radiological features which can help in differentiating the two conditions have been emphasized. This can avoid the delay in diagnosis and management which can prove critical. High index of suspicion with timely intervention is the key for optimizing outcome. A diagnosis of intussusception should always be considered in any preterm infant with suspected NEC.